Perlindungan Hukum Rahasia Dagang: Studi Kasus Pembocoran Rahasia Dagang Racikan Kopi CV Bintang Harapan - Agiya Syafindrayani; Allenta Elsa Brilyana; Andhari Rahmi; Emma Yunika (Lembaga Pusat Studi Sosial dan Humaniora [LPS2H], 2025)
This research examines the importance of protecting trade secret laws in Indonesia. Trade secrets are a form of intellectual property for companies that must be kept confidential. This study uses a qualitative approach with a case study method, which focuses on the case of Hi Pin. Hi Pin, a former employee of CV Bintang Harapan who was proven to have violated trade secrets by leaking information related to coffee production for personal gain. This case highlights the risks of trade secret violations by former employees and the impact on a company's reputation and finances. The Indonesian government, through Law no. 30 of 2000 concerning Trade Secrets, has established strict sanctions to protect trade secret owners.